Catalytic hydrothermal liquefaction of microalgae using nanocatalyst. (1st December 2016) - Saber, Mohammad; Golzary, Abooali; Hosseinpour, Morteza; Takahashi, Fumitake; Yoshikawa, Kunio
Highlights: Hydrothermal liquefaction was carried out for bio-oil production from microalgae. Nanocatalyst was applied to increase the bio-oil yield at low temperature. Catalytic hydrothermal liquefaction resulted in higher bio-oil yield. The highest bio-oil yield (30.0 wt%) was obtained at 250 °C by using Nano Ni/SiO2 . Nanocatalyst was recovered from the solid residue. Abstract: Due to exhaustibility of fossil fuels and their adverse effects on the environment, bio-oil has been considered as an alternative energy source for fuel applications. Currently, there are two main processes for bio-oil production: pyrolysis and hydrothermal liquefaction (HTL). The hydrothermal liquefaction is defined as biomass-to-liquid conversion route carried out in the hot compressed water with or without the presence of a catalyst. The major concern in HTL is the high pressure of the process which results in high capital cost of equipment. Thus, the process pressure and temperature should be reduced, but at a lower temperature, bio-oil yield is not high enough to make HTL an economical process for sustainable fuel production. In this research, we investigated the applicability of a nanocatalyst (nano-Ni/SiO2 ), an acid catalyst (synthesized zeolite), and an alkali catalyst (Na2 CO3 ) to increase the bio-oil yield at low temperatures (210 °C, 230 °C, 250 °C). The major result of this work was higher bio-oil yields with the order of nano-Ni/SiO2 > zeolite > Na2 CO3 in hydrothermal liquefaction of microalgae Nannochloropsis sp.. The highest bio-oil yield (30.0 wt%) was obtained at 250 °C by using Nano-Ni/SiO2 . Moreover, applying catalyst resulted in a decrease in the oxygen and the nitrogen contents of the bio-oil and consequently an increase in its heating value. The results of this research also suggest the possibility of nanocatalyst recovery for 2–3 times.